Temporal lobe dysplasia: a characteristic sonographic finding in thanatophoric dysplasia. (13th October 2014) - Wang, D. C.; Shannon, P.; Toi, A.; Chitayat, D.; Mohan, U.; Barkova, E.; Keating, S.; Tomlinson, G.; Glanc, P.
ABSTRACT Objective To determine the incidence of temporal lobe dysplasia (TLD) detected on prenatal ultrasound in thanatophoric dysplasia (TD) over an 11‐year period in a tertiary referral center. Methods An 11‐year retrospective review of perinatal autopsies from 2002 to 2013 was performed to identify cases of TD. The ultrasound images and corresponding reports of all TD cases were examined for the presence of TLD. The same set of images subsequently underwent a retrospective review by a perinatal radiologist with knowledge of the features of TLD to determine whether they could be identified. Results Thirty‐one cases of TD underwent perinatal autopsy, and prenatal ultrasound imaging was available for review in 24 (77%). Mean gestational age at diagnosis of TD was 21.3 (range, 18–36) weeks. TLD was identified and reported in 6/24 (25%) cases; all six cases occurred after 2007. Retrospective interpretation of the ultrasound images identified features of TLD in 10 additional cases. In total, 16/24 (67%) cases displayed sonographic evidence of TLD. Temporal trends showed that TLD features were present in 50% (5/10) of all TD cases between 2002 and 2006 and in 79% (11/14) of those detected between 2007 and 2013. Conclusions At present, the detection rate of TLD by ultrasound is low but may be increased by modified brain images that enhance visualization of the temporal lobes. Prenatal identification of TLD may help in the prenatal diagnosis of TD and thus provide more accurate prenatal counseling and guide molecular investigations to confirm the specific diagnosis of TD. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.